Modeling and Control of a Doubly-Fed Induction Generator for Wind Turbine-Generator Systems - Mouna Lamnadi; Mourad Trihi; Badre Bossoufi; Abdelkader Boulezhar (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper presents a vector control direct (FOC) of double fed induction generator intended to control the generated stator powers. This device is intended to be implemented in a variable-speed wind-energy conversion system connected to the grid. In order to control the active and reactive power exchanged between the machine stator and the grid, the rotor is fed by a bi-directional converter. The DFIG is controlled by standard relay controllers. Details of the control strategy and system simulation were performed using Simulink and the results are presented in this here to show the effectiveness of the proposed control strategy.